A case of AIDS-associated Kaposi's sarcoma arising in the palate - FUKUSHIMA, Yosuke; ABE, Takahiro; TOMITAKA, Yuko; IMAI, Kenichiro; YODA, Tetsuya; KOKABU, Shoichiro (Japanese Journal of Oral and Maxillofacial Surgery, 2006)
A 46-year-old homosexual man was referred to our department on a certain day in February, 2005, by his home dentist because of a mass on the left side of the palate. He had been aware of this mass since the end of December 2004. This mass was dark purple, 10×18mm in size, elastic soft, and irregular in shape with clear margins. At presentation, a biopsy was performed, and the mass was diagnosed as Kaposi's sarcoma. On 8th day, laboratory tests revealed that he was HIV-1 positive. On 18th day, the patient was referred to the department of internal medicine. Highly active antiretroviral therapy (HAART) was initiated on 32th day. A complete remission of oral Kaposi's sarcoma was achieved on 130th day.